Impact of CYP2C19, CYP3A4, ABCB1, and FMO3 genotypes on plasma voriconazole in Thai patients with invasive fungal infections - Sumonrat Chuwongwattana; Thawinee Jantararoungtong; Santirat Prommas; Sadeep Medhasi; Apichaya Puangpetch; Chonlaphat Sukasem (Wiley, 2020)
Abstract Voriconazole is the first‐line antifungal choice in the treatment of invasive fungal infections (IFIs). Single nucleotide polymorphisms (SNPs) in drug‐metabolizing and transporter genes may affect voriconazole pharmacokinetics. This study aimed to determine the frequency of the CYP2C19 rs4244285, rs4986893, rs72552267, and rs12248560, CYP3A4 rs4646437, ABCB1 rs1045642, and FMO3 rs2266782 alleles and determine the association between these genetic variants and voriconazole concentrations in Thai patients with invasive fungal infections. The study comprised 177 Thai patients with IFIs in whom seven SNPs in CYP2C19, CYP3A4, ABCB1, and FMO3 were genotyped using TaqMan real‐time polymerase chain reaction (RT‐PCR) 5´ nuclease assays, and voriconazole plasma concentrations were measured by high‐performance liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). Of the 177 patients included, 31 were <12 years and 146 were ≥12 years. The CYP2C19 allele frequencies were 0.29 for *2, 0.060 for *3, 0.003 for *6, and 0.008 for *17. The allele frequency of CYP3A4 (rs4646437) was 0.26, ABCB1 (rs1045642) was 0.36, and FMO3 (rs2266782) was 0.16. The median voriconazole dose/weight was significantly lower in patients aged ≥12 years when compared to the patients aged <12 years (P < .001). Patients aged <12 years with CYP2C19*1/*2 exhibited significantly higher median voriconazole plasma concentrations than those with the CYP2C19*1/*1 (P = .038). However, there were no significant differences in median voriconazole plasma concentrations among the CYP2C19 genotypes in the patients aged ≥12 years. There was a lack of association observed among the CYP3A4, ABCB1, and FMO3 genotypes on the plasma voriconazole concentrations in both groups of patients. Our findings indicate that voriconazole plasma concentrations are affected by the CYP2C19*2 allele in patients aged <12 years but not in patients aged ≥12 years.